Pengujian Distribusi Beban Web dengan Algoritma Least Connection dan Weighted Least Connection - Nongki Angsar (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
The increased of web traffic and the development of the network bandwidth is relatively faster than the development of microprocessor technology led to today's server platforms one point no longer adequate to meet the needs of system scalability web server. Multiple server platforms is the answer. One solution that has been known is a cluster-based web server system. This research would be testing a web workload distribution on a cluster-based web server system by means of generating HTTP workloads statically (with fast HTTP requests per second is fixed) and dynamic (with HTTP requests per second rapidly changing or ride on a regular basis ) from the client to a web server system pool. Followed by analysis of traffic data packets. And then compare the results of the testing of the web workload distribution among the Least Connection algorithm (without weights) and Weighted Least Connection algorithm (with weights).